2008
DOI: 10.1080/08820130802191334
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cells in the Regulation of Maternal Immune Responses to the Fetus During Mammalian Gestation

Abstract: Successful mammalian pregnancy relies on the action of sophisticated regulatory mechanisms that allow the fetus (a semi-allograft) to grow and develop in the uterus in spite of being recognized by maternal immune cells. Among several immunocompetent cells present at the maternal fetal interface, dendritic cells (DC) seem to be of particular relevance for pregnancy maintenance given their unique ability to induce both antigen-specific immunity and tolerance. Thus, these cells would be potentially suitable candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 124 publications
0
35
0
Order By: Relevance
“…sence at the fetal-maternal interface (11,31), the current study investigated the role of progesterone in modulating DC function. As a result, a number of key findings have arisen from our investigations: first, that the ability of progesterone to downregulate BMDC inflammatory cytokine production and costimulatory molecule expression depends in large part on what TLR is engaged; second, progesterone downmodulates some BMDC TLR-induced inflammatory mediators via the GR alone and others via the PR and the GR; and third, PR agonists sustain IRF-3 phosphorylation following TLR3 ligation but not TLR4 ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sence at the fetal-maternal interface (11,31), the current study investigated the role of progesterone in modulating DC function. As a result, a number of key findings have arisen from our investigations: first, that the ability of progesterone to downregulate BMDC inflammatory cytokine production and costimulatory molecule expression depends in large part on what TLR is engaged; second, progesterone downmodulates some BMDC TLR-induced inflammatory mediators via the GR alone and others via the PR and the GR; and third, PR agonists sustain IRF-3 phosphorylation following TLR3 ligation but not TLR4 ligation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during pregnancy, T regulatory cells specific for fetal allograft Ags are involved in expression of tolerance to the fetus (8,9). DCs have been demonstrated around the fetomaternal interface, and studies have shown that in this situation, their function is altered to favor production of regulatory cytokines, such as IL-10, and reduce secretion of inflammatory cytokines, such as IL-12 (10,11). The microenvironment created during pregnancy differs from the normal physiological situation, particularly with regard to circulating hormones, and levels of glucocorticoids, estrogen, and progesterone are all increased.…”
mentioning
confidence: 99%
“…These cells lack expression of CD19, CD209, and CD163 but express the combination of markers ITGAX + / CD14 + /CD4 + /CD83 + / CD86 + . The genes CLEC4C, THBD, CD1C, CD80, IL10, and IL12B that characterize some of the decidual DCs (Kammerer et al 2008;Talayev et al 2010) were not found. CD14 is often considered a marker of macrophages, with which dendritic cells are closely related.…”
Section: Maternal Cells Uterine Dendritic Cells (Dcs; Cluster 4)mentioning
confidence: 99%
“…21 DC-SIGN 1 DCs are also able to secrete IL-15 during decidualization and embryo implantation. 11,22 This secretion then recruits decidual NK cells to the endometrium 23 and upregulates CD56 expression. 24 Previous works state that decidua tissues from spontaneous abortions contain fewer DC-SIGN 1 iDCs compared with normal decidua, and iDC maturation and migration out of the decidual tissue to initiate an immune response might explain this phenomenon.…”
Section: Human Dcsmentioning
confidence: 99%